ANALISIS STRATEGI PUBLIC RELATIONS PT BPRS HIK CIBITUNG DALAM MEMPROMOSI-KAN PRODUK TABUNGAN MUDHARABAH BERJANGKA INVESTASI - Ladyday Pertiwi; Fajri Ryan Isnandar (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
PT. BPRS HIK Cibitung is a private company engaged in Islamic banking or Islamic financial services, where there is a lot of competition in the banking industry that is getting tougher. The emergence of other competitors made BPRS HIK Cibitung have to compete during the times. A public relations strategy is important for a company because it supports efforts to promote and market a product in this study using a qualitative approach. The method used is this research method uses phenomenology, data collection techniques through observation techniques, and interviews. The concept used in this research is the Public Relations concept presented by Thomas L. Harris, who explains that there are three tactics: Pull Strategy, Push Strategy, and Pass Strategy. Based on the research and analysis conducted, it can be concluded that PT BPRS HIK Cibitung has carried out three tactics from the concept of Thomas L. Harris in Promoting Futures Investment Mudharabah Savings. The strategy carried out by PT BPRS HIK Cibitung in promotion is considered effective, with the use of media that is carried out according to and on target to make PT BPRS HIK Cibitung increasingly known to the public.